Evaluation of single-incision apical vaginal suspension for treatment of pelvic organ prolapse. (April 2020) - Lin, Kun-Ling; Tang, Feng-Hsiang; Chou, Shih-Hsiang; Loo, Zi-Xi; Liu, Yi-Yin; Juan, Yung-Shun; Long, Cheng-Yu
Abstract: Objective: To present a comprehensive evaluation of anterior/apical and/or posterior prolapse repair systems with a focus on safety and surgical efficacy. Methods: Two hundred and twenty women with pelvic organ prolapse (POP) stage II–IV were referred for single-incision transvaginal mesh procedures in a single institution. Pre- and postoperative assessments included pelvic examination, urodynamic studies, and personal interviews about patients' quality of life and urinary symptoms. Results: The anatomical success rate was 92.3 % (203/220), regardless of primary or de-novo POP, at 12–38 month follow-up. The POP quantification parameters, except total vaginal length, improved significantly after surgery ( p < 0.05). Complications included bladder injury (one case), mesh exposure (six cases) and urinary retention that required intermittent catheterization (five cases). There were no cases of bowel injury during surgery. The results indicated that 29 % of patients had de-novo stress urinary incontinence and 7.7 % of patients had de-novo POP after surgery. Conclusion: The apical vaginal suspension system is a safe and effective procedure, creating good anatomical restoration and significant improvement in quality of life. However, the rate of de-novo POP in the anterior compartment of the vagina (31.8 %) seems high after treatment with apical and posterior prolapse repair systems.